The Tatar layer of words in the system of kinship terms of the Besermans - Sergey A. Maksimov (Publishing house "Sreda", 2023)
The purpose of this study is to identify and systematize the terms of kinship of Tatar origin in the Beserman dialect. The terms of kinship in the Udmurt language are relatively well studied. However, the terminology of Tatar origin as a separate lexico-semantic layer has not previously been considered in publications. Meanwhile, the study of such vocabulary can help shed light on the problems of the ethnogenesis of the Besermans, which is very important. This study was carried out mainly on the basis of T. I. Teplyashina's monograph "The Language of the Besermans" and her field notes. The goals were achieved using descriptive and statistical methods, as well as the method of etymological analysis. Thirty-two Beserman terms of Tatar origin were identified and systematized, which allowed a new look at Besermian-Tatar contacts. In one of the periods, Besermans and Tatars had very close relationships up to interethnic marriages. The presence of special terms denoting the relatives of the husband among the Besermans, which are absent in other Udmurt dialects but correspond to the terms of the Chepetsk Tatars, may indicate that not only Besermian women married Tatars, but also Tatar women married Beserman men.